2018
DOI: 10.1002/jmrs.300
|View full text |Cite
|
Sign up to set email alerts
|

3D printing and medical imaging

Abstract: Three‐dimensional (3D) printing and medical imaging have a complementary association, the benefits and application areas of which are increasingly documented and further illustrated in this journal publication. Medical imaging data can be appropriately processed (i.e. segmented) to provide the geometric information from which accurate and realistic 3D medical models can be generated. The resulting models can be printed in a range of different materials to suit their use as phantoms in medical radiation and ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 6 publications
1
17
0
1
Order By: Relevance
“…Use of three-dimensional (3D) printing in medicine has become popular for some years [1]. Examples of its applications include development of personalised medical devices and anatomical models for surgical planning, teaching and research [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of three-dimensional (3D) printing in medicine has become popular for some years [1]. Examples of its applications include development of personalised medical devices and anatomical models for surgical planning, teaching and research [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Use of three-dimensional (3D) printing in medicine has become popular for some years [1]. Examples of its applications include development of personalised medical devices and anatomical models for surgical planning, teaching and research [1][2][3][4][5][6][7]. Recently, studies have shown the use of 3D printing in anthropomorphic phantom development for quality assurance of medical radiation sciences procedures such as intensity modulated radiation therapy [8,9], stereotactic body radiation therapy [10], paediatric radiography [11], digital tomosynthesis [12][13][14] and computed tomography (CT) [2,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Ameliyathanelerde kullanılan cerrahi aletlerin üretimi için de oldukça kullanışlıdır. Teknoloji metal, seramik ve polimer malzemelere uygulanabilmekte, bu endüstri için yaygın olarak polimer malzemeler tercih edilmektedir [12][13][14][15][16][17][18][19][20]. Malzeme seçimi ve kullanım alanına göre çeşitli Eİ yöntemleri mevcuttur.…”
Section: Introductionunclassified
“…A variety of biomaterials (i.e., bioinks) have been used for tissue bioprinting, including ceramics, synthetic and natural polymers, decellularized tissues, and more frequently, hybrid bioinks consisting of a combination of these materials [8][9][10][11].While significant and rapid progresses have been made in tissue bioprinting processes for various in vitro applications, such as disease modeling [12] and drug screening [13], there are several challenges to address before bioprinting becomes clinically relevant [14][15][16]. These constraints include: 1) limited number of available bioink solutions and lack of thorough characterization of their biological and physiomechanical properties [10,17]; 2) poor understanding of the correlation between printed architecture and the ultimate tissue function [18,19]; 3) limitations on the quality of imaging techniques [20,21] and available bioprinters [22]; 4) complex and rather expensive processes involved pre, during, and post-bioprinting [22]; 5) suboptimal, non-specialized printing software and their often incompatibilities [23].There are eight articles published in this Special Issue composed of four research papers and four review papers. The research articles focus on the influence of electron beam (E-beam) sterilization on in vivo degradation of composite filaments [24], enhancing osteogenic differentiation of stem cells using 3D printed wavy scaffolds [25], the development of a scaffold-free bioprinter [26], and the fabrication of multilayered vascular constructs with a curved structure and multi-branches [27].…”
mentioning
confidence: 99%
“…While significant and rapid progresses have been made in tissue bioprinting processes for various in vitro applications, such as disease modeling [12] and drug screening [13], there are several challenges to address before bioprinting becomes clinically relevant [14][15][16]. These constraints include: 1) limited number of available bioink solutions and lack of thorough characterization of their biological and physiomechanical properties [10,17]; 2) poor understanding of the correlation between printed architecture and the ultimate tissue function [18,19]; 3) limitations on the quality of imaging techniques [20,21] and available bioprinters [22]; 4) complex and rather expensive processes involved pre, during, and post-bioprinting [22]; 5) suboptimal, non-specialized printing software and their often incompatibilities [23].…”
mentioning
confidence: 99%